Efficacy of medications in controlling cognitive dysfunction in Alzheimer’s : a systematic review - Sâmia Moreira de Andrade; Ítalo Sávio Mendes Rodrigues; Luís Marcelo Vieira Rosa; Rodrigo Luís Taminato; Gustavo Alves Andrade dos Santos (Dementia & Neuropsychologia)
ABSTRACT Dementia is one of the biggest global health crises of the 21st century. It is known that Alzheimer’s disease (AD) is the most common cause of dementia. Therefore, developing drugs with the potential to alter disease progression has been a priority. Objective: This study aims to review the efficacy and safety of drugs for AD. Methods: Based on the recommendations of the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) document, a systematic review was carried out in different databases. The Alzheimer’s Disease Assessment Scale (ADAS-Cog) was used as the primary outcome. The risk of bias was checked using the Risk of Bias in Randomized Trials (RoB 2). Results: A systematic review resulted in 64 articles which were included in the analysis. The main medications discussed were: donepezil, which demonstrated a significant improvement in cognitive function, with good tolerability, although it has limitations in patients with swallowing difficulties. Transdermal patches showed similar effectiveness and were recently approved. Galantamine showed benefits on cognitive function, with good tolerability. Rivastigmine was effective and presented in transdermal form with similar efficacy to capsules, but had mainly gastrointestinal adverse effects. Pioglitazone showed no significant results initially, but some studies suggest benefits in patients with AD associated with type II diabetes mellitus. Conclusion: The studies reviewed indicate that, although some current medications such as donepezil, galantamine, and rivastigmine have modest, well-established benefits in clinical practice, many new agents have not yet demonstrated significant efficacy in modifying AD progression.